1996
DOI: 10.1007/bf02931194
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mental arithmetic stress on blood cell counts and the immune system

Abstract: To determine whether acute mental stress alters the composition of peripheral blood cells or components of the immune system, we determined blood cell counts and leukocyte differential counts, and examined lymphocyte subsets, before, during, and after 10 min. of mental arithmetic in 20 healthy female students. During mental stress the absolute number of leukocytes, lymphocytes, CD8+ cells, and CD16+ cells increased significantly, and the rate of CD8+ cell increase was higher than CD4+ cell increase. Therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
1
3
0
1
Order By: Relevance
“…This equally reveals that the significant increase in lymphocytes is an adaptive response of the peripheral blood cells to infection, physiological, and immunological changes due to stress (Kondo and Morimoto, 1996). Similar hematotoxic effects have been observed by Yildirim et al (2018) and Mladenović et al (2014).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…This equally reveals that the significant increase in lymphocytes is an adaptive response of the peripheral blood cells to infection, physiological, and immunological changes due to stress (Kondo and Morimoto, 1996). Similar hematotoxic effects have been observed by Yildirim et al (2018) and Mladenović et al (2014).…”
Section: Discussionsupporting
confidence: 74%
“…Not only were Cd and Pb significantly increased in the serum of rats exposed to contaminated soil, the constituent of SEO induced lymphocytopenia at the same higher doses. This equally reveals that the significant increase in lymphocytes is an adaptive response of the peripheral blood cells to infection, physiological, and immunological changes due to stress (Kondo and Morimoto, 1996). Similar hematotoxic effects have been observed by Yildirim et al (2018) and Mladenović et al (2014).…”
Section: Discussionmentioning
confidence: 99%
“…China’s development comes an increasing pressure that can trigger higher levels of mental stress in both low-income and high-income groups. It is known that mental stress can affect health by inducing immunologic and cardiovascular changes [ 26 , 27 ]. If mental stress develops into a severe mental illness, it might become a risk factor associated with TB [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…[13] In contrast, increase in the absolute number of leukocytes, lymphocytes, CD8 + cells, and CD16 + cells observed during mental stress. [14] Interestingly, it was reported that effect Data were presented as mean±SD. TLC: Total leukocyte count, MV: Vestibular males, MC: Control males, D0: Pre-intervention score (during regular classes), D1: Post-intervention score (during regular classes), D2: Post-intervention scores (during pre-examination period), *P<0.05, **P<0.01, ***P<0.001 National Journal of Physiology, Pharmacy and Pharmacologyof stress on immunity varies based on the type of stress, as acute stress increases in natural immunity and decrease in specific immunity and exam stress mainly suppresses cellular immunity and chronic stress suppress both cellular and humoral immunity.…”
Section: Discussionmentioning
confidence: 99%